1981
DOI: 10.3109/17453678108992167
|View full text |Cite
|
Sign up to set email alerts
|

Evans' Repair of Lateral Instability of the Ankle Joint

Abstract: A follow-up study is presented of 26 ankle joints with recurrent lateral instability, treated with surgical repair by the Evans method. The median follow-up period was 3.1 (range 1.1-6.9) years. Normal stability was achieved in 73 per cent of the ankles, and another 12 per cent were improved. Similar results are obtained with other methods of surgical repair. Preoperatively 82 per cent of the joints had a positive anterior drawer symptom. This was only found in 12 per cent postoperatively, and these ankles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…9 Approximately the same percentage of patients with symptomatic ankle instability will be shown to be stable on stress radiographs. 19…”
Section: Discussionmentioning
confidence: 99%
“…9 Approximately the same percentage of patients with symptomatic ankle instability will be shown to be stable on stress radiographs. 19…”
Section: Discussionmentioning
confidence: 99%
“…Since then, many early clinical studies with short-term followup have reported good subjective results after the procedure, although residual anterior talar instability and reduced subtalar motion were observed. 39,66,82,101,126,138,140,148 Biomechanical analysis of the Evans procedure identified a propensity for increased anterior displacement, internal rotation, and tilt of the talus, as well as restriction of subtalar motion when compared to anatomic repair. 29,114 Ankle joint kinematics also can be permanently altered with the procedure.…”
Section: Nonanatomic Reconstructions (Table 5)mentioning
confidence: 99%
“…All the patients were called for re-examination 2 to 16 years postoperatively (average 8 years); 107 (94.7%) ankles of 103 patients could be reached for clinical re-evaluation. Three patients had died during the follow-up period and 3 could not be located.…”
Section: Materlal and Methodsmentioning
confidence: 99%